Kinetics of Surface-Driven Self-Assembly and Fatigue-Induced Disassembly of a Virus-Based Nanocoating - Valbuena, Alejandro (Biophys J, 2017)
Self-assembling protein layers provide a “bottom-up” approach for precisely organizing functional elements at the nanoscale over a large solid surface area. The design of protein sheets with architecture and physical properties suitable for nanotechnological applications may be greatly facilitated by a thorough understanding of the principles that underlie their self-assembly and disassembly. In a previous study, the hexagonal lattice formed by the capsid protein (CA) of human immunodeficiency virus (HIV) was self-assembled as a monomolecular layer directly onto a solid substrate, and its mechanical properties and dynamics at equilibrium were analyzed by atomic force microscopy. Here, we use atomic force microscopy to analyze the kinetics of self-assembly of the planar CA lattice on a substrate and of its disassembly, either spontaneous or induced by materials fatigue. Both self-assembly and disassembly of the CA layer are cooperative reactions that proceed until a phase equilibrium is reached. Self-assembly requires a critical protein concentration and is initiated by formation of nucleation points on the substrate, followed by lattice growth and eventual merging of CA patches into a continuous monolayer. Disassembly of the CA layer showed hysteresis and appears to proceed only after large enough defects (nucleation points) are formed in the lattice, whose number is largely increased by inducing materials fatigue that depends on mechanical load and its frequency. Implications of the kinetic results obtained for a better understanding of self-assembly and disassembly of the HIV capsid and protein-based two-dimensional nanomaterials and the design of anti-HIV drugs targeting (dis)assembly and biocompatible nanocoatings are discussed.